Collaborative school culture and educators’ job satisfaction relationship: gender as a moderator - Nikodemus Hans Setiadi Wijaya; Wisnu Prajogo; Heni Kusumawati (Problems and Perspectives in Management, 2020)
Job satisfaction is an important attitude of employees toward work contexts, which measures the effectiveness of various individuals in the workplace. Not surprisingly, studies on this topic were obtained by researchers on organizational behavior. This study deals with the association between collaborative school culture (CSC) and job satisfaction. In addition, gender is considered as a moderator. In total, 221 educators from high schools and universities took part in this study. It was revealed that CSC and its dimensions were positively associated with the educators’ job satisfaction. The moderating effect of gender on CSC and job satisfaction was partial. Gender was found to moderate the effects of teachers’ collaboration and unity of purpose learning on job satisfaction, namely, the impact of the variables on job satisfaction were lower for women respondents than for men respondents. This study contributes to theory by giving evidence on the importance of each specific cultural dimension for job satisfaction and the possible impact of gender on the relationships. Education practitioners should consider introducing such a culture into their institutions to increase educators’ job satisfaction.